Positive Reciprocal Feedback of lncRNA ZEB1-AS1 and HIF-1α Contributes to Hypoxia-Promoted Tumorigenesis and Metastasis of Pancreatic Cancer - Jin, Yan; Zhang, Zhengming; Yu, Qiao; Zeng, Zhu; Song, Hong; Huang, Xiaoxu; Kong, Qi; Hu, Hao; Xia, Yabin (Frontiers in Oncology, 2021)
Background: Many studies have reported the roles of the extracellular hypoxia microenvironment in the tumorigenesis and metastasis of multiple cancers. However, long noncoding RNAs (lncRNAs) that induce cancer oncogenicity and metastasis of pancreatic cancer (PC) under hypoxia conditions remain unclear. Methods: In PC cells, the expression levels of lncRNAs in different conditions (normoxia or hypoxia) were compared through RNA sequencing (RNA-seq). The effects of the zinc finger E-box binding homeobox 1 (ZEB1-AS1) antisense lncRNA on PC cells cultured in normoxia/hypoxia medium were measured through gain and loss-of-function experiments. Fluorescence in situ hybridization and luciferase reporter assays in addition to in vivo studies were utilized to explore the adaptive mechanisms of ZEB1-AS1 in the hypoxia-promoted proliferation, migration and invasion ability of PC cells. Moreover, the level of ZEB1-AS1 and associated targets or pathways were investigated in both PC and pancreatic normal tissues. Results: RNA-seq revealed that ZEB1-AS1 was significantly upregulated in PC cells under hypoxia conditions. The ZEB1-AS1 expression level was closely associated with poor prognosis of PC patients. Knockdown of ZEB1-AS1 suppressed the proliferation, migration and invasion of PC cells in vitro as well as PC xenograft tumor growth in vivo. In PC cells, RNAi-mediated reduction of ZEB1-AS1 inhibited zinc finger E-box binding homeobox 1 (ZEB1), while ZEB1-AS1 overexpression rescued ZEB1 expression, indicating that ZEB1-AS1 promotes ZEB1 expression. Moreover, HIF-1α induced the expression of ZEB1-AS1 by binding to the ZEB1-AS1 promoter, which contains a putative hypoxia response element (HRE). Mechanistically, ZEB1-AS1 scaffolded the interaction among hypoxia inducible factor-1α (HIF-1α), ZEB1 and histone deacetylase 1 (HDAC1), leading to deacetylation-mediated stabilization of HIF-1α. We further revealed that ZEB1 induced the deacetylase capacity of HDAC1 to suppress the acetylation or degradation of HIF-1α, improving HIF-1α assembly. Thus, hypoxia-induced ZEB1-AS1 facilitated ZEB1 transcription and the stability of HIF-1α, which promoted the metastasis of PC cells. Clinically, dysregulated ZEB1 and HIF-1α expression was significantly correlated with histological grade, lymphatic metastasis and distant metastasis in PC patients. Conclusions: Our results emphasized that the positive reciprocal loop of HIF-1α/ZEB1-AS1/ZEB1/HDAC1 contributes to hypoxia-promoted oncogenicity and PC metastasis, indicating that it might be a novel therapeutic target for PC.